ANALISIS PENGARUH ASPAL MODIFIKASI DENGAN PENAMBAHAN ABU CANGKANG SAWIT TERHADAP KINERJA PERKERASAN ASPAL - Agus Mahliza Fahmi; Irwan Irwan; Amsuardiman Amsuardiman (Universitas Medan Area, 2021)
This research uses oil palm shell ash as a filler of 1%, 2% and 3% of the weight and uses asphalt with 60/70 penetration, the method used is AASHTO and the specifications of Bina Marga 2018. This research was conducted to determine the characteristics and the optimum strength of the asphalt mixture using oil palm shell ash as a filler. From the resultsvof the tests that have been carried out, the averange value of the marshall test on the test object with 1% filler content is 290 kn/mm, the marshall value on the test object with a filler content 2% is 293 kn/mm, then the marshall value on the test object with a filler content of 3% is 293 kn/mm.